P‐69: Optical Diode Effect for the Shutter Glass Application by Plasma‐Treated Surface. Issue 1 (30th May 2018) - Jeong, Jinyoung; Choi, Hojin; Hyeon, Seung-Guk; Lee, Ji-Hoon
Abstract : We proposed a method to obtain the optical diode effect of nematic liquid crystal by treating plasma to one of the substrates. The sample became bright stage when a positive electric field was applied, while it became dark state when a negative field was applied. The result can be used for the shutter glass application of the 3D displays.